On continuity of homomorphisms between topological Clifford semigroups - Pastukhova, I. (Carpathian Mathematical Publications, 2014)
Generalizing an old result of Bowman we prove that a homomorphism f:X→ Y between topological Clifford semigroups is continuous if the idempotent band E_X={xX:xx=x} of X is a V-semilattice; the topological Clifford semigroup Y is ditopological; the restriction f|E_X is continuous; for each subgroup HX the restriction f|H is continuous.